Educação e economia solidária: contribuições da pedagogia da alternância para a formação dos catadores de materiais recicláveis - Mazzeu, Francisco José Carvalho [UNESP] (My University, 2010)
This text presents the Pedagogy of Alternating methodology, highlighting its contribution to re-think the formation of catadores of recycling materials (rubbish collectors). Whereas the use of this approach in the urban area is unusual, the goal of the article is to initiate a debate to promote further elaborations. Initially an overview of the Pedagogy of Alternating is presented and the main instruments used in this approach are commented. Two theoretical and methodological issues are indicated as challenges for catadores formation: the relations between Education and Work and the relations between Theory and Practice. The need to overcome dichotomy between these dimensions of human activity (that predominates in today's society) is defended. The catadores work reveals the exclusion of these workers of less organized sectors of production chains, with few opportunities to obtain better income and qualification. Overcome this gap requires an intense training to turn the catadores in recycling workers . To reach this goal the implementation of Alternating experiences between study and work in cooperatives and schools is not enough. A deep transformation is needed over the ways and subjects of both study and work, in order to create emancipating activities that promotes a full development of these workers.

Este texto destaca a metodologia da Pedagogia da Alternância, apontando contribuições dessa proposta para re-pensar a formação dos catadores de materiais recicláveis. Considerando que a utilização dessa abordagem na área urbana ainda é pouco comum, procura-se iniciar uma reflexão que provoque elaborações futuras. Inicialmente apresenta-se uma visão geral da Pedagogia da Alternância e são citados os principais instrumentos usados nessa abordagem. Em seguida, são destacados dois aspectos teórico-metodológicos que constituem desafios para o trabalho de formação de catadores de resíduos: as relações entre Educação e Trabalho e entre Teoria e Prática, apontando para a necessidade de superar a dicotomia entre essas dimensões da atividade humana que predomina na sociedade atual. O trabalho dos cata-dores revela a exclusão dos trabalhadores que atuam nos setores menos organizados das cadeias produtivas, com poucas oportunidades de qualificação e baixa renda. Superar esse abismo requer uma intensa formação para os trabalhadores da reciclagem. Para dar conta desse desafio sugere-se que não basta implementar processos de alternância entre estudo e trabalho nas cooperativas de catadores. É preciso transformar as formas e conteúdos tanto do estudo quanto do trabalho, para que se possam criar atividades emancipatórias em que essa alternância conduza efetivamente a um pleno desenvolvimento dos trabalhadores.
Education and solidary economy: contributions of the pedagogy of alternating to improve the rubbish collectors formation
Keywords: Solidary economy; Pedagogy of alternating; Catadores; Professional training; Economia solidária; Pedagogia da alternância; Catadores; Formação profissional